Types of organizational culture and sustainability in ecotourism businesses in southern Mexico - Medina-Álvarez, Efraín (2023)
Purpose: The purpose of this paper is to contribute to the understanding of the relationship between different types of organizational culture (hierarchical, clan or group, market or rational and adhocratic) and sustainability through three dimensions (economic, environmental and social) in ecotourism businesses in Oaxaca and Chiapas, Mexico. Design/methodology/approach: In this research 80 questionnaires were administered in the form of face-to-face interviews to ecotourism business owners'. Through a discriminant analysis and the theoretical support of the competing values framework (CVF), the prevailing types of culture were identified, and their influence was analysed through a regression analysis. Findings: The results show that ecotourism businesses which are driven by hierarchical culture tend to have a greater focus on economic sustainability, while those businesses with a market or rational culture show a positive and significant influence on environmental sustainability. Likewise, businesses with adhocratic culture achieve sustainability holistically; however, the data reveal that clan or group culture is not associated with social sustainability. Originality/value: This study offers empirical research that explains the relationship between organizational culture and sustainability. Additionally, it contributes to the study of environmental management issues in the ecotourism sector.